PENYANDINGAN ADAT KEDALAM HUKUM FIQH (Pemikiran Hukum Islam Prof. Dr. Hazairin, SH) - Adi Yono (Universitas Trunojoyo Madura, 2018)
Hazairin as a reformer of Islamic law in Indonesia better known as the father of bilateral inheritance theory and receptie exit has brought the influence of the era of independence, Islamic law has passed two periods. The First Period is the period of acceptance of Islamic law as a persuasive source in the context of constitutional law, ie a new source of law accepted if it is believed, for example, Islamic law has been included in the formulation of the Jakarta charter as one of the results of BPUPKI sessions. The Second Period is a period in which Islamic law as an authoritative source (lawful source of law) in the constitution, when the Presidential Decree of 5 July 1965 recognizing that the Jakarta Charter embodies the 1945 Constitution.Influence of Dr. Hazairin against the development of Islamic law in Indonesia until now (era of reform) is quite large, where the receptie exit theories have built a formation of